Global timing of hepatitis C virus elimination in high‐income countries. (23rd December 2019) - Razavi, Homie; Sanchez Gonzalez, Yuri; Yuen, Cammy; Cornberg, Markus
Abstract: Background & Aims: Introduction of highly efficacious pan‐genotypic therapies for hepatitis C virus (HCV) infection has made the elimination of the disease an attainable goal. This study assessed progress made in 45 high‐income countries towards meeting the World Health Organization's targets for HCV elimination by 2030. Methods: A Markov model developed to forecast annual HCV‐infected population was populated with demographic and epidemiological inputs, with historical incidence calibrated to reported prevalence of chronic HCV for each country. Future incidence was assumed to be a linear function of overall prevalence (or prevalence of minimal fibrosis in countries with treatment restrictions). 2017 levels of diagnosis and treatment were assumed constant in the future. The analysis estimated the year countries would meet HCV elimination targets for 80% reduction in incidence, 65% reduction in liver‐related deaths, 90% diagnosis coverage and 80% treatment among the treatment‐eligible population. Results: Of the 45 countries analyzed, nine (Australia, France, Iceland, Italy, Japan, South Korea, Spain, Switzerland and the United Kingdom) are on track towards meeting the HCV elimination targets by 2030. While Austria, Germany and Malta could also reach the targets with expanded screening efforts, 30 countries are not projected to eliminate HCV before 2050. Incidence was the most difficult target to achieve, followed by liver‐related deaths. Conclusions: Even with introduction of curative therapies, 80% of high‐income countries are not on track to meet HCV elimination targets by 2030, and 67% are off track by at least 20 years. Immediate action to improve HCV screening and treatment is needed globally to make HCV elimination attainable.